Circulating exosomes with unique lipid signature in relapsing remitting multiple sclerosis - Palazzo, Claudia; Asci, Ilaria; Russo, Silvia; Buccoliero, Cinzia; Mangialardi, Vincenzo; Abbrescia, Pasqua; Valente, Onofrio; Ruggieri, Maddalena; Paolicelli, Damiano; Lobasso, Simona; Frigeri, Antonio (Frontiers in Cellular Neuroscience, 2025)
Exosomes are small, membrane-bound vesicles secreted by most cell types into the extracellular environment. They play a crucial role in intercellular communication by transporting bioactive molecules, including proteins, lipids, and RNAs, thereby influencing the phenotype and potentially the genotype in recipient cells. In recent years, exosomes have gained increasing attention in the study of pathophysiological conditions and numerous diseases, including multiple sclerosis (MS), an autoimmune disorder with myelin sheath and neuroaxonal damage in the central nervous system. In this study, we isolated and purified serum-derived exosomes from patients with relapsing remitting MS (RR-MS) and characterized their lipid profiles using matrix-assisted laser desorption ionization-time-of-flight/mass spectrometry (MALDI-TOF/MS). Lipid analysis was performed in both negative and positive ion modes on intact exosomes, bypassing lipid extraction steps and significantly reducing sample-processing time. The lipid profiles of RR-MS exosomes were compared to those of exosomes isolated from the serum of healthy subjects (HS), and statistical analysis was applied to mass spectra to identify potential lipid biomarkers. The specific phospholipid marker of exosomal membranes, bis(monoacylglycero)phosphate (BMP), was clearly detected in both MALDI lipid profiles, with no significant differences in its content between the two sample groups. However, RR-MS exosomes exhibited significantly lower levels of phosphatidic acid (PA) compared to HS exosomes, despite PA being a key structural component of extracellular vesicles. Notably, comparative analysis revealed an enrichment of several lysophosphatidylcholine (LPC) species in RR-MS exosome membranes, aligning with their known proinflammatory role in MS pathology. Our most significant finding was a markedly lower phosphatidylcholine (PC) to LPC ratio in the pathological group indicating potential alterations in membrane lipid homeostasis. To the best of our knowledge, this study is the first to report a distinct lipid signature in serum-derived exosomes from RR-MS patients using direct MALDI-TOF/MS analysis.